Bibliometric Analysis of Problem Based Learning in Physics Education: A Scopus Based Study (1996-2023) - Siti Nurjanah; Jumriani Sultan; Siti Aisyah; Dita Puspita; Nur Ulyasari (Universitas Lambung Mangkurat, 2024)
Using the Scopus database, this study analyzed and mapped the productivity, citation patterns, and collaborative research on Problem-Based Learning (PBL) in Physics Education. The method used was bibliometric, using the Scopus database. A total of 58 articles published between 1996 and 2023 were analyzed. The findings indicate a steady increase in publications from 1996 to 2019, with a decline during the COVID-19 pandemic years. The Asia Pacific Forum on Science Learning and Teaching emerged as the leading journal, with major contributions from the State University of Surabaya and the University of Rwanda. The most influential authors and articles were identified, and key research trends were highlighted. This bibliometric analysis provides a foundation for future research on PBL approaches in physics education.